Byron and Marginality - Lennartz, Norbert (Edinburgh University Press, 2022)
Explores Byron as the figurehead of Romanticism and the writer of provocatively 'marginal' textsThis book approaches Byron from a completely new angle: no longer seen in terms of his status as a celebrity and a star on the book-selling market, Byron is instead seen as an outsider both in Regency society and, even more so, for his iconoclastic views of life and literature. Pilgrims in pursuit of non-existing shrines, women as man-eating giants and viragos, cannibalism, suicide, black humour and other provocatively border-crossing topics leave scholars hopelessly at a loss as to where they should categorise Byron and what they should do with his penchant for marginal themes, genres and characters. Byron caters to numerous Romantic clichés (weltschmerz, melancholy, subjectivity), while simultaneously reverting to genres, themes and motifs that cast him as a pre- or even anti-Romantic. This collection will trigger new debates in Byron scholarship and show that terms such as canonicity and marginality tend to be blurry and stand in constant need of re-negotiation.Key Features:Re-reads Byron's heterogeneous textsForegrounds Byron's marginal texts, the margins from which they were written and the thematic marginalities they deal withRe-evalutates Romanticism in the light of marginalityPinpoints the interface between Classicism, Romanticism and Modernity